Hubungan Antara Asupan Zink dengan Anemia pada Remaja di Sukoharjo, Jawa Tengah - Rizki, Meitanti Dinia, dr. M. Shoim Dasuki, M.Kes (2017)
Background: Changes in adolescence affects nutritional needs, absorption, and the way of usingnutrients. Nutritional problems commonly experienced by one of them is anaemia. Anaemia among adolescents can be caused by many things, such as inadequate intake of macronutrients and micronutrients, such as zinc. Zinc interact indirectly in the body that helps in the synthesis of the protein that carries iron. The purpose of this study is to determine the relationship between the zinc intakes with anaemia in adolescents in Sukoharjo, Central Java. Methods: This research is an analytic observational research with cross sectional approach. It conducted in SMP Muhammadiyah 1 Kartasura. The sample size used 65 selected people by using purposive technique sampling. The measurement of zinc intakes used FFQ method Semi-quantitative (SQ-FFQ). The data was analysed by Chi-square test using SPSS 22.0. Results: From the Chi-Square test, it was obtained p value of 0.02 (p <0.05). Students with good zinc intake and anaemia by 22 persons (75.9%) and less zinc intake and anaemiaby 19 persons (52.8%). It means that there is a relationship between the intakes of zinc with anaemia in junior high school students. Conclusion: There is a significant association between the intakes Zink with anaemia of students in junior high.